The Use of Bumper Wire Technique and Intravascular Ultrasound for Precise Aorto-Ostial Stenting - Reddy, Pavan K. V.; Daibes, Joseph; Skaf, Michel; Ochoa, Roberto; Fujisaki, Tomohiro; Lin, Patricia; Patel, Apurva; Kwan, Tak (Frontiers in Cardiovascular Medicine, 2022)
Background: Aorto-ostial interventions are challenging due to the limitations of contemporary equipment, imprecise ostial demarcation and problematic ostial lesion characteristics. Suboptimal stent placement is common and portends worse clinical outcomes. Procedural and long-term outcomes of the bumper wire technique with intravascular ultrasound (IVUS) assessment have not been investigated. Methods: A single center retrospective study was conducted. Patients who underwent ostial lesion percutaneous coronary intervention (PCI) with the bumper wire technique between January 2019 and September 2020 were identified. The primary endpoint was to determine the geographic miss rate defined by inadequate ostial coverage or excess stent protrusion >2mm by IVUS or angiography. The secondary endpoint was target lesion failure (TLF) at six months after PCI, defined as the composite of cardiovascular death, target-vessel myocardial infarction (MI), and target lesion revascularization. Results: In total, 45 patients were identified. The average age was 71.7 years old, and 85.4% were male. Indication for PCI was acute coronary syndrome in about a third of patients. 26 patients had left main ostial lesions and 19 patients had right coronary artery ostial lesions. Geographic miss was detected in two patients (4.4%): one patient (2.2%) had excess proximal stent protrusion and one patient (2.2%) had ostial miss. Six patients were lost due to follow up. TLF, stroke, or major bleeding were not observed in any patients. Conclusions: The bumper wire technique is safe and efficient with low rates of geographic miss or adverse clinical outcomes. This is the first study to confirm precise aorto-ostial stent implantation with the bumper wire technique using IVUS confirmation.